In vitro antiviral activity of fisetin, rutin and naringenin against dengue virus type-2 - Zandi, Keivan; Teoh, Boon Teong; Sam, Sing Sin; Wong, Pooi Fong; Mustafa, Mohd Rais; AbuBakar, Sazaly (2011)
In vitro antiviral activities of three flavonoids; fisetin, naringenin and rutin against DENV-2 (NGC strain) were evaluated. Inhibitory effects of each compound at the different stages of DENV-2 infection were examined using foci forming unit reduction assay (FFURA) and quantitative real-time polymerase chain amplification (qRT-PCR). Fisetin, rutin and naringenin showed cytotoxic effects against Vero cells with 50% cytotoxicity (CC50) values of 247, >1000, and 87 µg/mL, respectively. Fisetin when added to Vero cells after virus adsorption inhibited DENV replication with a half maximal inhibition concentration (IC50) value of 55 µg/mL and selectivity index (SI) of 4.49. The IC50 value of fisetin was 43.12 µg/mL with SI=5.72 when Vero cells were treated for 5 h before virus infection and continuously up to 4 days postinfection. There was no direct virucidal activity or prophylactic activity of fisetin against DENV-2. Rutin and naringenin did not inhibit DENV-2 replication in Vero cells. Naringenin however, exhibited direct virucidal activity against DENV-2 with IC50 = 52.64 µg/mL but the SI was <1. The present study suggests that among the flavonoids examined, only fisetin showed significant in vitro anti dengue virus replication activity.